Estudio de factibilidad socio económico para la creación de un centro ocupacional para las personas con discapacidad intelectual que son atendidos por la Fundación María Montessori de la ciudad de Otavalo - Bonifaz Vaca, Patricia Liceth (2015)
The embodiment of the present study aims to give the Maria Montessori Foundation a reliable social and economic study such that the creation of occupational center a reality that benefits people with intellectual disabilities in the city of San Luis de Otavalo. This study by conducting a series of analyzes aims to determine the feasibility of creating an occupational center for people with intellectual disabilities who are serviced by the Maria Montessori Foundation Otavalo, in order to provide a new occupational training option. For the creation of occupational center it has a firm proposal for funding from international organizations nonprofit domiciled in our country and in the same foundation, seeing the latent need of the population with disabilities are willing to deliver and manage resources for this study reach your big goal. That's why the administrative and teaching staff of the foundation work every day to improve current living conditions of people with intellectual disabilities who attend the foundation. The occupational center is aimed at empower people with intellectual disabilities who have completed basic education stage, and whose condition cannot access higher education. The occupational center will initially charge a monthly pension established by the Ministry of Education is the regulatory body, which must be filled by representatives of the beneficiaries of the service.